Fluid flows to black holes : a tribute to S. Chandrasekhar on his birth centenary - Saikia, D. J.; Trimble, Virginia; Chandrasekhar, S. (Subrahmanyan), 1910-1995.; Chandrasekhar Centennial Symposium (2010 : University of Chicago) (Singapore : World Scientific)
Includes bibliographical references and index